The Successful Treatment of Aquired Inhibitors Against Factor VIII. - Brackmann, H.-H.; Etzel, F.; Hofmann, P.; Fgli, H. (Thrombosis and Haemostasis, 1977)
From the 582 inhibitor tested hemophilia A patients 19 were found to have an inhibitor against factor VIII. In 2 years of study the observation has been made, that a specific therapy combination of an activated prothrombin complex (Fraction Feiba) with high dosages of factor VIII concentrate can reduce the inhibitor titer to sero. A modified method of Bethesda was used for the detection of inhibitors. An inhibitor concentration of 1 U/ml was determined when the patients plasma inactivated 75% of that activity of factor VIII in the incubation mixture after the incubation time at 37° C. The combination therapy dosages for Fraction Feiba range from 30 to 120 U/kg body-weight and for factor VIII concentrate from 40 to 150 U/Kg bodyweight. The dosages are given 2 to 3 times a day in cases of acute bleeding episodes, and 3-7 times a week durincr regular prophylactic treatment to remove the inhibitor. In 11 of our 19 inhibitor patients, the inhibitor titer was reduced to sero on the basis of this combination therapy. High and low responsers were recorded, the highes response being 147 U/ml. The remaining (8) patients are still undergoing treatment with this procedure.